KIAI LEADERSHIP IN FORMING DISCIPLINE FOR STUDENTS IN ISLAMIC BOARDING SCHOOL - almada, sirin; Abdullah Aminuddin Aziz; Arini Elya Nura Hanun (STAI Ma'had Aly Al-Hikam Malang, 2025)
This study discusses the role of kiai leadership in shaping the character of santri discipline. Kiai as a charismatic figure is not only a spiritual leader, but also a role model that is emulated in everyday life. Exemplary behavior is the main strategy in instilling discipline without coercion. The application of discipline is carried out through rules, educational sanctions, and the habituation of spiritual activities such as dhikr and tawassul. This effort not only regulates external behavior, but also forms an inner attitude that is voluntarily obedient. Challenges such as laziness and differences in the background of students are overcome through a consistent and humanistic approach. The case study research method is used in this study, so that several research steps ranging from interviews, documentation, and observations are carried out so that researchers conduct interactive analysis by Miles and Huberman, conclusions are drawn by researchers carefully and in accordance with applicable scientific principles. The results of the study show that the combination of inspiring leadership, a clear rule system, and intensive spiritual guidance can create the character of students who are disciplined, responsible, and independent. Keywords: Kiai leadership; role model; discipline; character; spirituality Abstrak Penelitian ini membahas peran kepemimpinan kiai dalam membentuk karakter disiplin santri. Kiai sebagai sosok kharismatik tidak hanya menjadi pemimpin spiritual, tetapi juga panutan yang dicontoh dalam keseharian. Keteladanan menjadi strategi utama dalam menanamkan kedisiplinan tanpa paksaan. Penerapan disiplin dilakukan melalui aturan, sanksi yang bersifat mendidik, dan pembiasaan kegiatan spiritual seperti dzikir dan tawassul. Upaya ini tidak hanya mengatur perilaku lahiriah, tetapi juga membentuk sikap batiniah yang patuh secara sukarela. Tantangan seperti rasa malas dan perbedaan latar belakang santri diatasi melalui pendekatan yang konsisten dan humanis. Metode penelitian studi kasus digunakan dalam penelitian ini, sehingga beberapa langkah penelitian mulai dari wawancara, dokumentasi, dan observasi dilakukan sehingga peneliti melakukan analisis secara interaktif milik Miles dan Huberman, kesimpulan ditarik oleh peneliti secara seksama dan sesuai dengan kaidah ilmiah yang berlaku. Hasil penelitian menunjukkan bahwa kombinasi antara kepemimpinan yang inspiratif, sistem aturan yang jelas, dan pembinaan spiritual yang intensif mampu menciptakan karakter santri yang disiplin, bertanggung jawab, dan mandiri. Kata Kunci: Kepemimpinan kiai; keteladanan; disiplin santri; karakter; spiritualitas